Patrolling the homeland - Parsons, John Richard, author.
1 online resource
Keywords: "Patrolling the Homeland explores the tension surrounding the militarization of national borders through the perspective of US militia volunteers. Amidst a humanitarian crisis in which more than 7,800 people have lost their lives attempting to cross the border, US militias patrol the deserts along the Mexican border in camouflage, armed with assault rifles and night-vision goggles to "protect" the US. How and why US border militias conduct their activities is paramount to understanding similar movements, ideologies, and rhetoric around the world that oppose the movement of refugees and support the closing or restriction of international and regional borders. Based on extensive and engaging ethnography, Patrolling the Homeland explores not how people strive to be moral but how they maintain their self-perception as already and always moral individuals in spite of evidence to the contrary. This book signifies a creative and unique addition to morality and ethics through an honest and critical examination of a unique social movement indicative of contemporary society. A valuable read for anthropologists, sociologists, criminologists, and individuals interested in morality and ethics, militias, border studies, and policing"--